Religious Cultural Development Model (SosPem-KPPB) In Improving The Quality Of Graduates - Amrullah Amrullah; Baharuddin Baharuddin; Muhammad Walid (Universitas Nurul Jadid, 2025)
Study This aim For find the formation model of religious implementation culture, as well as implications for the development of religious on the rise quality of graduates of Islamic education institutions. The study uses a qualitative multisite study design. The study involved madrasah-level middle schools in the Pasuruan and Surabaya areas. Data were collected through in-depth interviews, passive participatory passive, and study documentation with single- site and cross -site model analysis to obtain a comprehensive conceptual model. Triangulation was used as a knife analysis end For get conclusion. Research results show that the formation of religion in madrasah began from strengthening the vision of founders, Islamic boarding school values, as well as demands from society, which then internalized into vision, mission, and programs of the madrasah. Implementation of religious realized through habituation of worship, role models, ethics communication, discipline, and formation of Islamic character. Development culture religious done by adapting Kurt Lewin's change model, called with development model culture religious in the aspects of socialization and Habituation through Exemplary behavior, strengthening organizational culture, as well as Continuous Supervision (SosPem -KPPB). The model has proven capable of creating a safe, comfortable, and conducive learning environment, improving learning quality, strengthening Power reason participant educate, and impact positive to improvement quality of graduates in academic and non-academic aspects.